The Influence of Using TikTok Social Media on Students' Social Interaction Levels - Nisa, Sofiatun; Mohamed, Hasnah; Yamkasikorn, Montree (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to determine the effect of the level of use of TikTok social media on the level of students' social interaction. Methodology: This type of research is quantitative with the expost facto method. The technique used in sampling is the purposive sampling technique with a sample size of 79 students. Instruments and data collection techniques were carried out using a questionnaire on the use of social media TikTok and social interaction. The data analysis technique used in this study is simple linear regression analysis with the help of the SPSS 24 program. Main Findings: The study revealed that the influence of TikTok usage on the social interaction of Grade VII students at State Junior High School 17 Jambi City is 11.2% (or 0.112), which falls into the low but significant category. The level of TikTok use among students is 63.89%, categorized as high, while their level of social interaction is also high at 64.57%. Although the direct influence of TikTok on social interaction is relatively low, the high usage level warrants attention. Therefore, parents and guidance and counseling teachers are encouraged to supervise and monitor students' activities on social media to ensure it remains positive and constructive. Novelty/Originality of this study: It is expected to add new insights and knowledge about the influence of social media on students' social interactions, so that teachers can work together with parents to help monitor children's social relationships.